A Study of Functional Outcome of Retrograde Intramedullary Interlocking Nailing in Treatment of Supracondylar Femoral Fracture - Kandel, Prakriti Raj; Shrestha, Bipan; Shrestha, Kishor Man; Chaudhary, Pritam (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTIONFractures of the distal femur are usually sustained from high velocity trauma in adults and trivial fall in elderly. These fractures are usually associated with severe degree of comminution and intra-articular involvement. Therefore, anatomical reduction of fracture fragments, restoration of limb length, and early mobilization are key factors for optimal outcomes of involved limb. This longitudinal study was intended to evaluate the functional outcome of distal femoral fracture in adults managed surgically by Retrograde Nail.MATERIAL AND METHODSThis prospective and observational hospital based study was carried out in Orthopedics Department, Universal College of medical Sciences-Teaching Hospital (UCMS-TH) from July 2020 to June 2021. All patients with traumatic distal femoral fractures (AO/OTA type A) who fulfilled the inclusion criteria were enrolled in the study and were treated surgically by Retrograde Nail. Fracture was classified according to AO/OTA classification and functional outcome was assessed according to Neer’s scoring system. Post-operatively patients were regularly followed at 6 weeks, 3 months and 6 months.RESULTSIn this study of 30 cases, male to female ratio was 3:2 with mean age of 39.47 years. Road Traffic Accident (RTA) was most common mode of injury. The functional outcome evaluated according to Neer’s scoring system was found good result in 43.3%, excellent in 36.7%, fair in 16.7% and poor in 3.3%. The mean Neer’s score was 78.9.CONCLUSIONDistal femoral fractures (AO/OTA type A) when treated with retrograde nailing has good to excellent functional outcome in majority of cases with minimal manageable complication.